Automatic Control of Hydroponic Plant Ph Levels Using Sensor Sku Sen 0161 - Nurul Yaqin; Ahmad Fawaid Zuhri; Tholib Hariono (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
The hydroponic method of growing has developed rapidly in recent years because it can save agricultural land. Hydroponic planting systems need to pay more attention to the pH content of the water because water is the main factor for the growth of hydroponic plants. So far, hydroponic owners still use manual methods to monitor Ph levels in the water, measuring PH levels using a PH meter and then giving a solution to lower or increase PH levels according to the measurement results. This activity must be done regularly to maintain plant fertility. This research develops a solution in the form of a tool to control the PH level of the water automatically using the SKU SEN 0161 sensor. This sensor works by checking the PH level of the water. If the PH level of the water is too low (acidic), then the alkaline solution pump will turn on to increase the PH level of the water. If the PH level of the water is too high, then the acid solution pump will turn on to lower the PH level of the water. To get good measurement results, a PH sensor calibration process is carried out using a linear regression method by comparing the voltage data from the sensor with the water PH data measured using a PH Meter. From the results of testing the accuracy of the water PH sensor, it has good accuracy with an average error of 0.51%.